Pyrosequencing Uncovers a Shift in Bacterial Communities Across Life Stages of Octodonta nipae (Coleoptera: Chrysomelidae) - Ali, Habib; Muhammad, Abrar; Sanda, Nafiu Bala; Huang, Ying; Hou, Youming (Frontiers in Microbiology, 2019)
Bacterial symbionts of insects affect a wide array of host traits including fitness and immunity. Octodonta nipae (Maulik), commonly known as hispid leaf beetle is a destructive palm pest around the world. Understanding the dynamics of microbiota is essential to unravel the complex interplay between O. nipae and its bacterial symbionts. In this study, bacterial 16S rRNA V3-V4 region was targeted to decipher the diversity and dynamics of bacterial symbionts across different life stages [eggs, larvae, pupae and adult (male and female)] and reproductive organs [ovaries and testis] of O. nipae. Clustering analysis at ≥97% similarity threshold produced 3,959 operational taxonomic units (OTUs) that belonged to nine different phyla. Proteobacteria, Actinobacteria, and Firmicutes represented the bulk of taxa that underwent notable changes during metamorphosis. Enterobacteriaceae and Dermabacteraceae were the most abundant families in immature stages (eggs, larvae, and pupae), while Anaplasmataceae family was dominated in adults (male and female) and reproductive organs (ovaries and testis). The genus Serratia and Lactococcus were most abundant in eggs, whereas Pantoea and Brachybacterium represented the bulk of larvae and pupae microbiota. Interestingly the genus Wolbachia found positive to all tested samples and was recorded extremely high (>64%) in the adult and reproductive organs. The bacteria varied across the developmental stages and responsible for various metabolic activities. Selection choice exerted by the insect host as a result of its age or developmental stage could be the main reason to ascertain the shift in the bacteria populations. Maternally inherited Wolbachia was found to be an obligate endosymbiont infecting all tested life stages, body parts, and tissues. These outcomes foster our understanding of the intricate associations between bacteria and O. nipae and will incorporate in devising novel pest control strategies against this palm pest.